STRATEGI MENINGKATKAN KEBERHASILAN AKREDITASI PERPUSTAKAAN MELALUI PENGUATAN KERJA TIM DI BALAI LITBANG AGAMA MAKASSAR - Jeni Bunga; Dorkas (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article discusses the strategy of strengthening teamwork as a key factor in improving the success of library accreditation, with a case study at the Makassar Religious Research and Development Center. Library accreditation is an important process in ensuring the quality of information services in accordance with the National Library Standards (SNP). In the context of a complex and often hierarchical government bureaucracy, teamwork plays a central role in effectively formulating, implementing, and evaluating the entire accreditation process. This study uses a descriptive qualitative approach with data collection methods through in-depth interviews, observations, and documentation studies. The results of the analysis show that the success of accreditation is greatly influenced by factors such as clear division of tasks, open team communication, participatory leadership, and institutional policy support. The strategy of strengthening teamwork through training, reward systems, and the creation of a collaborative work culture has been shown to increase the effectiveness and efficiency of the accreditation process. These findings indicate that in government bureaucracy, organized and structurally supported teamwork can be a strong foundation in building professional and high-standard library services. This article recommends the integration of teamwork into the managerial system of government institutions as a sustainable effort to improve the quality of public services, especially in the library sector